Fibrous dysplasia on the skull - Sarkar, S; Mazumder, U; Rahman, KM; Azam, MG (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):55-9.The abstract of this article is available on the PubMed website